Pesantren Pespektif Historis: Memahami Ragam Tipologi Dan Perkembangan di Indonesia - Zakki, Mohammad; Hazinah, Hazinah (Molang: Journal Islamic Education, 2023)
Islamic boarding schools with all their limitations at the time they were just founded had a sizable contribution to the development of the Indonesian nation and state. The indicator is that many people are able to practice religious teachings and create peace in life amidst differences in religion, ethnicity, race and culture, as well as the increasing number of educational institutions and centers for the spread of Islam. This research uses a qualitative approach with the type of library research or library research. The purpose of this research is to trace the history, development and contribution of Islamic boarding schools to the Indonesian nation. The results are: Islamic boarding schools that are developing in Indonesia include Islamic boarding schools in the form of salaf, Modern Islamic boarding schools and convergence Islamic boarding schools. The contribution of pesantren to Indonesia is that there are many educational institutions and citizens who actively participate in practicing religion and creating a peaceful life.